Zarządzanie kosztami jakości a koncepcje TQM i kaizen - Nowak, Edward (Quality cost management vs TQM and kaizen conceptions, 2009)
The paper discusses cost management in quality management. The concept of total quality management is depicted. The importance of cost information in TQM conception is shown. Also the concept of the continuous improvement is shown as well as the methods of quality cost reduction. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, Nr 53, s. 94-100